Internal dynamics of inorganic and methylmercury in a marine fish: Insights from mercury stable isotopes. (December 2020) - Lee, Bong Joo; Kwon, Sae Yun; Yin, Runsheng; Li, Miling; Jung, Saebom; Lim, Seung Hyeon; Lee, Ju Hyeon; Kim, Kang Woong; Kim, Kyoung Duck; Jang, Ji Won
Abstract: Mercury isotope ratios in fish tissues have been used to infer sources and biogeochemical processes of mercury in aquatic ecosystems. More experimental studies are however needed to understand the internal dynamics of mercury isotopes and to further assess the feasibility of using fish mercury isotope ratios as a monitoring tool. We exposed Olive flounder ( Paralichthys olivaceus) to food pellets spiked with varying concentrations (400, 1600 ng/g) of methylmercury (MeHg) and inorganic mercury (IHg) for 10 weeks. Total mercury (THg), MeHg concentrations, and mercury isotope ratios (δ 202 Hg, Δ 199 Hg, Δ 200 Hg) were measured in the muscle, liver, kidney, and intestine of fish. Fish fed mercury unamended food pellets and MeHg amended food pellets showed absence of internal δ 202 Hg and Δ 199 Hg fractionation in all tissue type. For fish fed IHg food pellets, the δ 202 Hg and Δ 199 Hg values of intestine equilibrated to those of the IHg food pellets. Kidney, muscle, and liver exhibited varying degrees of isotopic mixing toward the IHg food pellets, consistent with the degree of IHg bioaccumulation. Liver showed additional positive δ 202 Hg shifts (∼0.63‰) from the binary mixing line between the unamended food pellets and IHg food pellets, which we attribute to redistribution or biliary excretion of liver IHg with a lower δ 202 Hg to other tissues. Significant δ 202 Hg fractionation in the liver and incomplete isotopic equilibration in the muscle indicate that these tissues may not be suitable for source monitoring at sites heavily polluted by IHg. Instead, fish intestine appears to be a more suitable proxy for identifying IHg sources. The results from our study are essential for determining the appropriate fish tissues for monitoring environmental sources of IHg and MeHg. Graphical abstract: Image 1 Highlights: Marine fish was exposed to food pellets amended with inorganic and methylmercury. All fish tissues equilibrated isotopically to dietary methylmercury. Only fish intestine equilibrated isotopically to dietary inorganic mercury (IHg). Redistribution or biliary excretion of IHg explains liver isotope fractionation. Abstract : Mercury isotope fractionation in fish liver suggests liver cannot be used as a conservative proxy for IHg pollution. Fish intestine is a better proxy for tracing IHg sources.